Impact of emergency computed tomography on treatment and time to treatment for renal colic - Maria Utter; Fredrik Altmark; Marcin Popiolek; Andreas Forsvall; Karl-Johan Lundström; Tomas Thiel; Magnus Wagenius (Scandinavian Journal of Urology)
Objective: The aim of this study was to evaluate the utilization and impact of emergency computed tomography (CT) on the management of renal colic, focusing on treatment decisions, time to treatment and the subsequent need for additional emergency department (ED) visits.